An Islamic Political Jurisprudence Analysis of Reproductive Health Services under Article 103(4)(e) of Government Regulation No. 28/2024 - Hidayat, Yoga Mai; Khairina, Khairina; Husni, Alfi; Yustiloviani, Yustiloviani; Rizal, Deri (UIN Mahmud Yunus Batusangkar, 2025)
This study examines the provision of reproductive health services as stipulated in Article 103 Paragraph (4) Letter e of Government Regulation (PP) No. 28 of 2024, focusing specifically on the distribution of contraceptives to school-aged children and adolescents. The research investigates the background and rationale behind the issuance of this regulation and analyzes it through the lens of fiqh siyasah (Islamic political jurisprudence). Employing a qualitative normative approach, this study is based on library research by systematically reviewing relevant literature, including books, scholarly articles, journals, and official publications. The researcher acts as the primary research instrument.The findings suggest that the emergence of this provision is influenced by several urgent social issues: the rise in teenage promiscuity, high rates of abortion among adolescents aged 15–19, an increasing number of marriage dispensations due to premarital sexual activity, and efforts to reduce the transmission of sexually transmitted diseases (STDs), including HIV/AIDS. From the perspective of fiqh siyasah, the legality of contraceptive distribution depends on the marital status of the recipients. For married adolescents, the use of contraceptives is considered permissible. However, for those who are unmarried, it is deemed impermissible (haram) as it potentially facilitates or legitimizes acts of zina (adultery), which are prohibited in Islamic law.